The Lost Track of Time - Britt, Paige; White, Lee 1970- (New York Scholastic Press, 2015)
Penelope is an imaginative girl, whose every day has been rigidly scheduled by her mother--until one day she falls through a hole in her calendar and lands in the Realm of Possibility, where she discovers that it, too, is stuck in a track of time, and only she can save it.
Keywords: Time -- Juvenile fiction; Imagination -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Time -- Fiction; Imagination -- Fiction; Self-actualization (Psychology) -- Fiction; Mothers and daughters -- Fiction